(untitled) (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2022)
Developing creativity in early childhood is important to do in addition to exploring their interests and talents but also for developing cognitive abilities. Developing creativity in the school environment can be done by providing a place for creative work, one of which is a wall magazine or mading. Given the importance of the goals and benefits of mading in the school environment, mading empowerment should be done. Mading in addition to containing written works can also contain other works in two-dimensional form, adjusted to the environment where the mading is made. Efforts to empower mading were also carried out by the ABA V Kedung Peluk Kindergarten environment, the works published were not written works but children’s creative works in the form of drawings or other works of art. To get works that can be published in the mading, it is necessary to explore concepts that are appropriate to their age and are not monotonous. In addition to this, mading management is also needed, to make the mading interesting to look at and maintain the work after it is installed on the mading.